Potent effects of dioscin against pancreatic cancer via miR‐149‐3P‐mediated inhibition of the Akt1 signalling pathway. (14th February 2017) - Si, Lingling; Xu, Lina; Yin, Lianhong; Qi, Yan; Han, Xu; Xu, Youwei; Zhao, Yanyan; Liu, Kexin; Peng, Jinyong
Abstract : Background and Purpose: The aim of the present study was to investigate the effects and possible underlying mechanisms of dioscin against pancreatic cancer in vitro and in vivo . Experimental Approach: In vitro actions of dioscin on viability of ASPC‐1 and PANC‐1 cells, and in vivo effects to suppress the tumour growth of cell xenografts in nude mice were assessed. In addition, microRNA microarray analysis determined which microRNAs were affected by dioscin. The mechanisms underlying the actions of dioscin against pancreatic cancer were elucidated in terms of Akt1 and other proteins related to aopoptosis. Key Results: Dioscin markedly induced apoptosis and significantly suppressed the tumour growth of ASPC‐1 and PANC‐1 cell xenografts, in nude mice. Total of 107 microRNAs with differential changes were found, in which miR‐149‐3P targeted with Akt1 was markedly up‐regulated by dioscin. Further studies showed that dioscin significantly down‐regulated Akt1 levels, and thus induced cell apoptosis by increasing the levels of Bax, Apaf‐1, cleaved caspase‐3/9, cleaved PARP, suppressing Bcl‐2 levels, and causing cytochrome c release. The effects of an inhibitor of miR‐149‐3P and of siRNA of testicular Akt1 suggested that dioscin showed excellent activity against pancreatic cancer via miR‐ 149‐3P‐mediated inhibition of Akt1 signalling pathway. Conclusions and Implications: Collectively, these findings confirmed the potent effects of dioscin against pancreatic cancer and also provided novel insights into the mechanisms of the compound as a potential candidate for the treatment of pancreatic cancer.